PDG Characterization of an EDFA Developed for CATV Application DOI: 10.14209/jcis.2002.2 - C. Fugihara, Meire; J. Kalinowski, Hypolito; Müller, Márcia; L. Fabris, José; Arellano, Walter (Journal of Communication and Information Systems, 2015)
Results for the Polarization Dependent Gain (PDG) of an Erbium-Doped Fiber Amplifier, aimed to cable television distribution networks (CATV), are described. PDG measurements are done by switching the state of polarizarion of the launched signal between two orthogonal states, for several wavelengths and signal input powers. The obtained results show that the amplifier has very low PDG. 0.0279 ± 0.0012 dB.